SYSTEMIC APPROACH TO SUBSTANTIATING NEW AND IMPROVED EXISTING TECHNOLOGIES FOR CONDITIONING MULTI-COMPONENT UNDERGROUND WATERS (Municipal economy of cities. Series: «Economy science», 2018)
By results of monitoring the quality state of underground waters of settlements in northern-western regions of Ukraine the necessity is determined for their comprehensive treatment from different iron forms, from ammonia nitrogen, dissolved organic matter, phenols for conducting stabilization processing. The analysis carried out of existing know-how showed its inefficiency for the comprehensive treatment of the said pollutions. The aim of the paper is the development of the systemic approach to improving the selection of technologies in preparing multi-component underground waters under conditions of increased anthropogenic loading. The proposed systemic approach is based on the comprehensive use of biophysical-chemical methods for treating underground multi-component waters with subsequent stabilization processing. Main issues are: the implementation of monitoring the changing parameters of water quality; the determination of the interconnection between polluting substances and basic physico-chemical parameters of underground water quality; the establishment of classes and subclasses of underground waters; the determination of the possibility of implementing the synergy effect in developing technological schemes; the use of matrix structures of biominerals for removing heavy metals ions (Cr6+, Ni2+, Cu2+, Zn2+); the determination of the necessity in correcting values of pH-Eh, bicarbonate alkalinity; the determination of basic oxidizer in a system; the determination of the necessary number of devices and their levels necessary for changing phase-dispersion state of system state; the use of new bioreactor designs, of hydrodynamic cavitators, of devices for their hydro-automatic washout. The systematization is done of the method of biochemical destruction and oxidization of ferrum-organic complexes and iron hydrocarbonates. This systematization is based on separating iron- and manganese oxidizing bacteria into chemoautotrophs - Gallionella ferruginea; chemoorganotrophs - Leptothrix ochracea, Leptothrix thrichogenes, Crenotrix; and organotrophs - Arthobacter. The choice is systematized of methods, processes, devices and reagents for treatment. The specifics of this systematization is the totality of detailed differentiation of parameters of natural waters quality in pH, permagnate oxidation, bicarbonate alkalinity, content of compounds of Fe, NH3, NH4+, C6H5OH and in methods, processes, devices, reagents necessary for water treatment. Keywords: multi-component underground waters, systemic approach to improving know-how